When Gen Z Leads Millennials: The Intergenerational Communication Gap at PT Nutrifood - Alyda Khairunnisa; Harry Isra Muhammad; Silviana Purwanti; Dony Kristian (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2026)
This study examined the dynamics of intergenerational communication gaps between Generation Z as leaders and Millennials as employees at PT Nutrifood Indonesia, East Kalimantan Region. The communication gap was analyzed in relation to the internalization process of the ICARE culture (Integrity, Collaboration, Innovation, Respect, and Excellence) owned by PT Nutrifood Indonesia. The purpose of this study is to understand the dynamics and identify the factors of communication gaps between Gen Z Leaders and Millennial employees and also analyze how organizational culture values are internalized through intergenerational communication processes. This study employed a descriptive qualitative approach using a case study method, with data collected through in-depth interviews and direct observation. The analytical framework utilized the concept of communication barriers and structuration theory as the theoretical foundation. For the data analysis technique, this study employed the Miles and Huberman technique, consisting of data collection, data condensation, data display, and conclusion drawing/verifying. The findings revealed that Gen Z and Millennials tend to conform whenever they face communication barriers. Such conformity is manifested in cultural, language, and physical barriers that occur in PT Nutrifood Indonesia. The results shed light upon the dialectics of agency and structure in managing the generation gap in which a shift in values occurs towards the ICARE values as a structure that can be reproduced as a result of the duality that takes place.